2021
DOI: 10.3389/fmolb.2021.685938
|View full text |Cite
|
Sign up to set email alerts
|

Role of Calpain-1 in Neurogenesis

Abstract: While calpains have been implicated in neurogenesis for a long time, there is still little information regarding the specific contributions of various isoforms in this process. We took advantage of the availability of mutant mice with complete deletion of calpain-1 to analyze its contribution to neurogenesis. We first used the incorporation of BrdU in newly-generated cells in the subgranular zone of the dentate gyrus to determine the role of calpain-1 deletion in neuronal proliferation. Our results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Calpain also degraded calpastatin, leading to the breakdown of intracellular structures. In medicine, calpain regulates important cellular processes through selective and limited target cell cleavage after the increase of Ca 2+ [ 24 ]. However, under conditions of sustained Ca 2+ increase, calpain proteolysis becomes excessive and its targets undergo extensive degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Calpain also degraded calpastatin, leading to the breakdown of intracellular structures. In medicine, calpain regulates important cellular processes through selective and limited target cell cleavage after the increase of Ca 2+ [ 24 ]. However, under conditions of sustained Ca 2+ increase, calpain proteolysis becomes excessive and its targets undergo extensive degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The L domain is involved in tight binding to the active site of calpain [ 42 ]. PKA can catalyze the phosphorylation of the L domain of calpastatin, thereby affecting the ability and specificity of calpastatin to inhibit calpain activity [ 24 ]. In the development of drugs, it has been found that the N-terminal regulatory domain of calpastatin undergoes selective splicing compared to the conserved and repetitive four inhibitory domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During neuronal development, calpains participate in various processes such as neurite outgrowth, axon guidance, synaptogenesis, and dendritic spine formation. Calpain-mediated proteolysis is required for the dynamic rearrangement of the cytoskeleton, which is essential for neurite extension and growth cone guidance ( 39 ). By cleaving cytoskeletal proteins, calpains modulate the stability and plasticity of neuronal structures.…”
Section: Calpain In Neuronal Developmentmentioning
confidence: 99%
“…More specifically, they remove distinct motifs and domains from their target proteins, thereby modulating their structure, function, and activity (Sorimachi et al, 2011 ; Ono et al, 2016 ). They participate in a variety of vital cellular processes, including cell cycle and proliferation, apoptosis, cell motility, signal transduction pathways (Goll et al, 2003 ), neurogenesis (Baudry et al, 2021 ), and synaptic plasticity (Baudry and Bi, 2016 ). Based on their wide spectrum of cellular functions, disruption, and dysregulation of calpains are associated with various diseases (Ono et al, 2016 ).…”
Section: Calpainsmentioning
confidence: 99%